PRZYGOTOWANIA CYWILNE – NATOWSKA CYWILNA ZDOLNOŚĆ EKSPERCKA - Jacuch Andrzej (2020)
The article introduces the NATO civil preparedness tools, which support countries own planning and preparedness with the aim to strengthen collective defence. It analysis NATO’s civil expert capability and its applicability to support Polish civil and military bodies. The results of the survey among Polish transport experts are presented.